Carthage, Tunisia. The Carthage Circus Project: Aims, Strategy and Results - Bockmann, Ralf (e-Forschungsberichte des DAI, 2017)
The project studies the circus of Carthage, the biggest monument of the Roman city and the only one not excavated until now. The circus lay in the south western quarter of the ancient city, and the project analyses how the building changed the whole region and its urban patterns and infrastructure. We are looking at the diachronic development in this part of Carthage, from the Punic epoch through Roman times into Late Antiquity and Early Middle Ages in the only part of the city not overbuilt and not extensively studied.